Productivity of Zakat Institutions in Indonesia: A Comparison - Fatimah Iskandar Putri (Islamic Social Finance, 2022)
Zakat institutions play an important role in managing zakat productively, with the aim that the funds collected can be distributed in an appropriate manner to achieve welfare and social justice. The purpose of this research is to analyze the productivity of zakat institutions in Indonesia using the Malmquist Productivity Index (MPI) method with the 2016-2020 research period. The research object used is 15 zakat institutions in Indonesia. The data from this study comes from the annual financial reports of each institution from the 2016-2020 period. The input variables used are total assets, operational costs, and employee costs. Meanwhile, the output variable used is the amount of collection and distribution of zakat. The results of the study show that in general, zakat institutions experience increased productivity over time. Zakat institutions originating from mass organizations have the highest average productivity compared to other organizations. If productivity is seen from year to year in each institution, the institution with optimal productivity in all years of observation is LAZ Al-Azhar.